2015
DOI: 10.1136/thoraxjnl-2015-207770.2
|View full text |Cite
|
Sign up to set email alerts
|

T2 Vitamin D supplementation reduces perioperative systemic and alveolar inflammation in patients undergoing oesophagectomy: Results of the Vindaloo Trial

Abstract: Vitamin D deficiency is associated with increased risk of ARDS post-oesophagectomy. We recruited patients to a double-blind, randomised controlled trial of high dose Vitamin D supplementation 3–14 days pre-oesophagectomy.79 patients were randomised to receive placebo or 300,000 IU oral Vitamin D liquid 3–14 days prior to oesophagectomy. Blood samples were collected pre-dose, post-dose (pre-op) and post-op and analysed for 25-OH and 1,25-dOH Vitamin D, inflammatory cells and cytokines. Broncho-alveolar lavage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…A murine model study also found that dietary-induced vitamin D deficiency contributes to exaggerated alveolar inflammation, epithelial damage, and hypoxia [ 10 ]. Similar results have emerged from researchers who reported that many esophagectomy patients suffer from ARTI and ARDS in the post-operative environment, and vitamin D supplementation during pre-operative days appears to reduce the risk of ARTI and ARDS in those cohorts [ 60 ]. They also found that vitamin D supplementation increased the concentration of 25-hydroxyvitamin D and 1,25 dihydroxy vitamin D in affected patients, which contributed to reduced lung inflammation [ 60 ].…”
Section: The Influence Of Vitamin D In Reducing Arti and Ardssupporting
confidence: 82%
See 1 more Smart Citation
“…A murine model study also found that dietary-induced vitamin D deficiency contributes to exaggerated alveolar inflammation, epithelial damage, and hypoxia [ 10 ]. Similar results have emerged from researchers who reported that many esophagectomy patients suffer from ARTI and ARDS in the post-operative environment, and vitamin D supplementation during pre-operative days appears to reduce the risk of ARTI and ARDS in those cohorts [ 60 ]. They also found that vitamin D supplementation increased the concentration of 25-hydroxyvitamin D and 1,25 dihydroxy vitamin D in affected patients, which contributed to reduced lung inflammation [ 60 ].…”
Section: The Influence Of Vitamin D In Reducing Arti and Ardssupporting
confidence: 82%
“…Apart from the effects of COVID-19, general respiratory tract infections occur worldwide, causing millions of fatalities annually (2.8 million in 2010) [ 58 ]. There have been several articles published, which have shown the relationship between vitamin D levels in the body and the potential occurrence of ARTI and ARDS [ 10 , 31 , 59 , 60 , 61 , 62 ].…”
Section: The Influence Of Vitamin D In Reducing Arti and Ardsmentioning
confidence: 99%
“…We conducted a phase 2 randomized, placebo-controlled trial to test our hypothesis that high-dose cholecalciferol treatment preoperatively reduces markers of alveolar epithelial lung injury seen post esophagectomy, a high-risk population of developing ARDS. Results of these studies have been previously reported in the form of an abstract ( 26 ).…”
mentioning
confidence: 97%
“…Her group previously reported that vitamin D deficiency appears to contribute to the development of acute respiratory distress syndrome (ARDS)3 and now demonstrate that vitamin D supplementation reduces perioperative extravascular lung water but not oxygenation 1. The immunomodulatory effects of vitamin D (or the absence of them) have been a recurring theme of our 3 years reporting from the BTS Winter Meeting and we look forward to large confirmatory studies 4 5.…”
Section: Introductionmentioning
confidence: 84%
“…Dr Rachel Dancer (Birmingham University) received the BLF award for demonstrating that vitamin D supplementation reduces extravascular lung water, a surrogate marker of lung injury, after oesophagectomy in the VINDALOO trial1 (confirming Birmingham as the home of UK Indian Cuisine after the equally delicious BALTI trial!2). Her group previously reported that vitamin D deficiency appears to contribute to the development of acute respiratory distress syndrome (ARDS)3 and now demonstrate that vitamin D supplementation reduces perioperative extravascular lung water but not oxygenation 1.…”
Section: Introductionmentioning
confidence: 99%